Presence of Borrelia in different populations of Ixodes pararicinus from northwestern Argentina - Saracho Bottero, Maria Noelia; Sebastian, Patrick Stephan; Carvalho, Luis A.; Guardia Claps, Leonor; Mastropaolo, Mariano; Mangold, Atilio Jose; Venzal, José Manuel; Nava, Santiago (2017)
This work was performed to evaluate the presence of Borrelia in different populations of Ixodes pararicinus from northwestern Argentina (Jujuy, Salta and Tucumán provinces). Questing adults and nymphs of I. pararicinus were collected from vegetation, and I. pararicinus nymphs were also collected on birds. Eighty-two ticks were tested for Borrelia presence by PCR targeting the gene flagellin and the rrfA-rrlB intergenic spacer region. Pools of ticks positive to Borrelia were formed by two nymphs collected on Turdus rufiventris in Tucumán, one nymph collected on Syndactyla rufosuperciliata in Jujuy, one nymph collected on Turdus nigriceps in Tucumán, three nymphs collected on T. nigriceps in Tucumán, and two females collected from vegetation in Salta. Two haplotypes of Borrelia sp. belonging to the Borrelia burgdorferi sensu lato complex were found. One of them is closely related to the haplotypes of Borrelia genospecies previously reported in I. aragaoi from Uruguay (haplotypes D and E) and in I. pararicinus from Jujuy Province in Argentina. The second haplotype (detected in the sample of Salta) is closely related to the haplotypes A, B and C associated with I. aragaoi from Uruguay. All these results suggest that the presence of B. burgdorferi s.l. genospecies in I. pararicinus ticks is widespread along the entire distribution of this tick species in northwestern Argentina. However, the Borrelia presence in I. pararicinus cannot be directly assumed as a phenomenon of medical relevance, because Ixodes ticks are not relevant as human parasites in South America, and none of the two Borrelia genospecies detected in this work is related to any of the Borrelia genospecies currently known to be pathogenic to humans.